(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the correlation between APRI, FIB-4, and ALBI scores with Child-Pugh classification in cirrhotic patients treated at Thai Binh General Hospital. Subjects and Methods: A cross-sectional descriptive study was conducted on 302 cirrhotic patients at Thai Binh General Hospital. The APRI, FIB-4, and ALBI scores were used to classify patients into Child-Pugh groups (A, B, C) and analyze the correlation with the Child-Pugh score. Results: The APRI, FIB-4, and ALBI scores showed significant differences between the Child-Pugh groups (A, B, C), with APRI and FIB-4 values progressively increasing from group A to group C, while ALBI decreased. These scores demonstrated a strong correlation with the Child-Pugh score (APRI: r = 0.635, FIB-4: r = 0.612, ALBI: r = 0.846; p < 0.001). Conclusion: The APRI, FIB-4, and ALBI scores are closely correlated with the Child-Pugh classification in cirrhotic patients and may be useful tools for evaluating the degree of cirrhosis and classifying patients.